Begrundelse for det performatives æstetik - Fischer-Lichte, Erika; Lauenstein Led, Jens Christian (Peripeti, 2024)
The well-known German professor of Theatre Research, Erika Fischer-Lichte, argues for the necessity of developing a specific performative aesthetics capable of reflecting the transformative processes and physical reactions which the audience experiences in the face of the rise of performative art forms.